PENINGKATAN KEMAMPUAN BERBICARA UNGGAH-UNGGUH RAGAM KRAMA DI KELAS X8 SMAN 8 SEMARANG DENGAN MEDIA KARTU PEMBERIAN PERAN - Muhammad Ali Said; Nunung Nilasari; Eka Yuli Astuti (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2025)
IMPROVING THE ABILITY TO SPEAK IN VARIOUS RULES IN CLASS X8 OF SMAN 8 SEMARANG USING ROLE CARD MEDIAMany students currently use Javanese without paying attention to the correct rules. They often equate the language used both with friends and with older people, namely dominantly using the ngoko variety. Researchers assume that this cannot be separated from the influence of modernization flows in various aspects as well as their social environment which does not support Javanese. One of the efforts made is to improve students' speaking skills through role assignment cards. In simple terms, the application of the Role Giving card media in this classroom action research is that students create conversation scenarios in Javanese according to the cards that have been prepared by the teacher. The card contains a conversation scenario between two people about something. Next, students are allowed to improvise according to the given theme. Teachers evaluate students' work results by expanding the scope of lessons according to predetermined material. The indicator of success in improving student learning outcomes in this research was seen from 75% of students passing the KKM (with a score of 75). The research results obtained from posttest data show that in the pre-cycle there were 40% (14 people) of students who completed the KKM. Then, in cycle 1 there were 69% (24 people) of students who completed the KKM. Then, in cycle 2 there were 89% (31 people) of students who completed the KKM. The data shows an increase from pre-cycle to cycle 2. And the success of the research is in accordance with the success indicators obtained during cycle 2, namely 89% of students completed the KKM or more than 75% of students completed the KKM.